The importance of change management in increasing school resilience: Insights from Indonesian schools in Saudi Arabia - Sukirjo, Sukirjo; Dwiningrum, Siti Irene Astuti; Purwanta, Edi; Sholeh, Badrus; Sutikno, Sutikno (LPMPP Universitas Negeri Yogyakarta, 2025)
School resilience must be strengthened for schools to be resilient and adaptable to change. To improve school resilience, change management is required. School resilience will be effective if teacher and student resilience supports it. Strengthening bonding, setting clear and consistent boundaries, teaching life skills, providing caring and support, setting and communicating high expectations, and offering opportunities for meaningful participation are all components of school resilience. On the other hand, individual resilience consists of seven components: emotional regulation, impulse control, empathy, optimism, causal analysis, self-efficacy, and reaching out. If there is a synergy of work at the macro, mezzo, and micro levels, the school resilience policy will be formed. This research aims to determine the level of school resilience and the change management strategies needed to strengthen the resilience of Indonesian schools in Jeddah, Saudi Arabia. The sequential explanatory mixed method approach (Cresswell) was used as the research method, and the subjects of this study were Saudi Arabia teachers and high school students. The findings of this study concluded that the average school resilience profile, as perceived by teachers and students, was in the moderately resilient category, which aligned with the individual resilience levels of teachers and students. In order to strengthen all aspects that must be owned by the school, such as the existence of fundamental values, synergy of social roles, development of competencies and skills, literacy knowledge, social punishment, and the existence of excellent programs sustainably designed by schools, the school must be able to apply the phases of change management supported by the synergy between roles.